Social Support and Quality of Life in Cancer Patients: A Study of Palliative Shelters in West Java - Rahayuwati, Laili; Pahria, Tuti; Ibrahim, Kusman; Nurhidayah, Ikeu; Agustina, Habsyah Saparidah (International Journal of Psychosocial Rehabilitation, 2020)
The risk of lifestyle and environment will lead to an increase in cancer prevalence. Therefore, it needs managing support for palliative cancer patients. The purpose of the study was to obtain the correlation between social support characteristics and cancer patients’ quality of life. This research using a cross-sectional approach was conducted in several palliative shelters. Samples were 93 respondents, obtained using a quota sampling technique. The variables used were social support (family, friends, and others) and the cancer patient's quality of life. The results showed that social support received at a high level was most obtained from the family as many as 65 respondents (69.9%). Furthermore, the social support factor of cancer patients related to the quality of life was friends' support (p-value